Analisis Strategi Marketing Mix dalam Meningkatkan Volume Penjualan Pada Rena Factory Outlet Di Kabupaten Tuban - Fitriatin, Dina; Syahrinullah, Syahrinullah (Journal of Management Branding, 2025)
In a competitive business environment, increasing sales volume is one of the main goals for the company, including the Rena Factory Outlet in Tuban Regency. This research focuses on the implementation of a marketing mix strategy that includes products, prices, distribution, and promotions as an effective way to achieve increased sales. This study aims to investigate how the implementation of a marketing mix strategy can increase the sales volume of Rena Factory Outlet by analyzing factors that affect consumer preferences and purchasing patterns in the local market. A qualitative descriptive approach is used to explore the meaning of social issues related to the marketing mix strategy at Rena Factory Outlet. The data was collected through observations and interviews with employees and consumers, and was supported by secondary data from various documents and references. Data analysis techniques include data reduction, data presentation, and drawing conclusions to simplify information into a more managed form. The results of the study show that the implementation of a marketing mix strategy that includes high-quality products, competitive prices, efficient distribution, and effective promotion has succeeded in increasing sales volume at Rena Factory Outlet. Products that match market needs, attractive prices, strategic locations, and creative promotions have increased brand awareness and consumer buying interest.  This research provides valuable insights for Rena Factory Outlet management in designing and implementing more effective marketing strategies. In addition, this research can be used as a reference for marketing practitioners and academics in understanding the dynamics of retail marketing at the local level, emphasizing the importance of an integrated approach and focusing on customer needs to achieve success in a competitive market